Lahore in Motion: Infrastructure, history and belonging in urban Pakistan - Maqsood, Ammara; Moffat, Chris; Sajjad, Fizzah (UCL Press, 2025)
Lahore in Motion provides a portrait of the Pakistani metropolis by tracing the path of the city's first metro rail corridor. Construction for this major piece of public infrastructure began in 2015 and, over subsequent years, the nascent ‘Orange Line’ rapidly reconfigured Lahore’s urban landscape – displacing residents and slicing through existing structures along its route, all while offering Lahoris the promise of ‘world-class’ public transportation. The volume collects stories from a series of walks along the metro’s 27-kilometre path, bringing together a wide variety of authors – including academics and activists, architects and artists – to reflect on the relationship between urban change and belonging in a historic city. Each chapter is organised around a particular station on the metro, but the volume moves far beyond the neighbourhoods shadowed by the train’s elevated track. Contributors navigate the friction generated by the Orange Line’s construction and reflect on how this project of connection both responds to and produces fragmentation in the urban environment. The book brings together critical insights on the politics of infrastructure in South Asia and the desires and dispossessions fuelling projects of development in the Global South, assessing how they unevenly inflect the intimate rhythms of everyday life in one of the world’s most populous cities. Praise for Lahore in Motion ‘This brilliant collection of essays written by a stellar bunch of academics and practitioners is a critical addition to the expanding knowledge frontier on infrastructure and cities in Pakistan. Anchored in the mega-infrastructure project the Orange Line, the stories unfold at multiple scales and bring to life the contradictory effects of infrastructure's longstanding promise of a better urban future.’ Nausheen Anwar, author of Infrastructure Redux: Crisis, Progress in Industrial Pakistan and Beyond ‘A lovely, mind-boggling tapestry of a book. Lahore in Motion gives us sharp, short glimpses into how Lahore lives, dies, plays, goes to work, prays, celebrates, resists and surrenders. Intimate forays into how a city reinvents itself, struggles to breathe and remembers that other imagined Lahore of legends.’ Mohammed Hanif, author of Rebel English Academy ‘Unfolding the personal and neighbourhood frictions lived along the Orange Line, a sensitive, accessible and scholarly portrait of contemporary city life emerges in these pages as a choir of discordant voices ruminate on the practical and symbolic logics of urban infrastructure.’ Caroline Knowles, author of Serious Money: Walking Plutocratic London ‘A compelling journey with electric insights about Lahore’s old and new geographies one metro station at a time. Each author provides an intricate and personal gateway into the city to muse and reflect on how people live, aspire and remember.’ Rashmi Sadana, author of The Moving City: Scenes from the Delhi Metro and the Social Life of Infrastructure